2020
DOI: 10.3390/jcm9124009
|View full text |Cite
|
Sign up to set email alerts
|

Asthma-Like Features and Anti-Asthmatic Drug Prescription in Children with Non-CF Bronchiectasis

Abstract: Bronchiectasis and asthma may share some characteristics and some patients may have both conditions. The present study aimed to examine the rationale of prophylactic inhaled corticosteroids (ICS) prescription in children with bronchiectasis. Data of children with radiologically established bronchiectasis were retrospectively reviewed. Episodes of dyspnea and wheezing, spirometric indices, total serum IgE, blood eosinophil counts, sensitization to aeroallergens, and air-trapping on expiratory CT scans, were rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Among our patients five children also had a history of recurrent wheezing during first years of life, many patients (73%) experienced wheezing during exacerbations and 6 had a diagnosis of asthma. Several studies have shown that, in daily medical practice, ICS with or without LABA, are commonly prescribed in patients with NCFB even without a diagnosis of coexisting asthma [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among our patients five children also had a history of recurrent wheezing during first years of life, many patients (73%) experienced wheezing during exacerbations and 6 had a diagnosis of asthma. Several studies have shown that, in daily medical practice, ICS with or without LABA, are commonly prescribed in patients with NCFB even without a diagnosis of coexisting asthma [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both asthma and non-cystic fibrosis bronchiectasis are chronical diseases affecting pediatric population, with great impact in their quality of life, in addition to economic and financial impact to their family and health system [ 12 14 , 19 ]. Its association, despite being described in literature, requires better comprehension about the pathophysiology involved.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that non-cystic fibrosis bronchiectasis in children is caused by repeatedly episodes of external agents associated with genetic vulnerability, however, the other possible etiologies are poorly defined, with heterogeneous risk factors [4,10]. Diagnosis consists of evaluating the patient's clinical condition and the results of computed tomography, but it is possible to observe that children with bronchiectasis also develop similar symptoms to asthma, which can be easily confused [4,[11][12][13][14].…”
Section: Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…Quite often the diagnosis of asthma is based on a therapeutic trial of ICS and an assessment of the child’s response. Nevertheless, this approach is not always helpful in children with bronchiectasis because of the confounding effect of co-administered drugs [ 26 ].…”
Section: Discussionmentioning
confidence: 99%